Allosteric modulation of Ras and the PI3K/AKT/mTOR pathway: emerging therapeutic opportunities - Hubbard, Paul A.; Moody, Colleen L.; Murali, Ramachandran (Frontiers in Physiology, 2014)
GTPases and kinases are two predominant signaling modules that regulate cell fate. Dysregulation of Ras, a GTPase, and the three eponymous kinases that form key nodes of the associated phosphatidylinositol 4,5-bisphosphate 3-kinase (PI3K)/AKT/mTOR pathway have been implicated in many cancers, including pancreatic cancer, a disease noted for its current lack of effective therapeutics. The K-Ras isoform of Ras is mutated in over 90% of pancreatic ductal adenocarcinomas (PDAC) and there is growing evidence linking aberrant PI3K/AKT/mTOR pathway activity to PDAC. Although these observations suggest that targeting one of these nodes might lead to more effective treatment options for patients with pancreatic and other cancers, the complex regulatory mechanisms and the number of sequence-conserved isoforms of these proteins have been viewed as significant barriers in drug development. Emerging insights into the allosteric regulatory mechanisms of these proteins suggest novel opportunities for development of selective allosteric inhibitors with fragment-based drug discovery helping make significant inroads. The fact that allosteric inhibitors of Ras and AKT are currently in pre-clinical development lends support to this approach. In this article, we will focus on the recent advances and merits of developing allosteric drugs targeting these two inter-related signaling pathways.